2023
DOI: 10.3920/bm2022.0053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of personalised therapy for the patients with irritable bowel syndrome

Abstract: Intestinal microbiota correction in the therapy of irritable bowel syndrome (IBS) is an important medical problem. We conducted a laboratory and pilot clinical trial to investigate the effect of autoprobiotic bacteria, indigenous bifidobacteria and enterococci isolated from faeces and grown on artificial media to use as personified food additives in IBS treatment. Convincing evidence of the clinical efficacy of autoprobiotic was demonstrated by the disappearance of dyspeptic symptoms. The microbiome of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…The same model shows a beneficial effect of autoprobiotics on intestinal motility [70]. Also, we demonstrated that autoprobiotic intake contributes to a decrease in dyspeptic symptoms and is associated with positive changes in the gut microbiota content [71,72], as well as the vaginal microbiota content [73].…”
Section: Discussionsupporting
confidence: 64%
“…The same model shows a beneficial effect of autoprobiotics on intestinal motility [70]. Also, we demonstrated that autoprobiotic intake contributes to a decrease in dyspeptic symptoms and is associated with positive changes in the gut microbiota content [71,72], as well as the vaginal microbiota content [73].…”
Section: Discussionsupporting
confidence: 64%
“…Promising results are obtained with clinical isolates of autologous probiotic microorganisms, e.g., non-toxigenic enterococci from the patients' microbiota, aiming for treatment of intestinal bowel syndromes, both in experiment and in clinical settings. These data are also reviewed elsewhere in literature [34].…”
Section: Malnutrition Factors Associated With Diarrheamentioning
confidence: 86%